Pengembangan Instrumen Performance Assessment Berbantuan Komputer pada Materi Optik, Kalor dan Listrik - Nuril Munfaridah; Putri Risky Hardita; Sentot Kusairi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
The aim of this research is to develop assessment models that can measure students’ performances and the effectiveness of the performance assessment instruments on the physics topic: the formation of image by the lens, specific heat and Ohm's law. This study used a research and development (R & D) design. The research steps consisted of preliminary study, the design of computer assisted-assessment performance instruments, the development of the performance assessment instruments draft, field trial, the development product revision and limited trial. The lecturer and the teacher validated the product of this study. The field trials on the legibility of performance assessment instruments for physics teacher and 5 senior high school in grade XI students. The data was collected by filling the feedback from the validator and field trial on students. The result of this study is a computer assisted-assessment performance that can measure the performance capabilities and provide feedback to students. Based on the result of feasibility test, the computer assisted-assessment performance instruments obtained a score of 3.4 (from maximum scale 4) and the teachers’ guidebooks of computer assisted-assessment performance instruments obtained average rating of 3.68 (from maximum scale 4). The computer assisted-assessment performance instruments measured the students’ performance capabilities effectively and be able to give feedback appropriately. The advantages of this assessment model is it caused this instruments are completed with guidebooks and the teacher can give fe simplicity of the use due to the instruments are completed by the guidebooks and directly give the feedback. The disadvantage of this assessment models is the limited scope of topics.